Characteristics of alkali species release from a burning coal/biomass blend. (1st April 2018) - Liu, Yingzu; He, Yong; Wang, Zhihua; Xia, Jun; Wan, Kaidi; Whiddon, Ronald; Cen, Kefa
Highlights: Investigate the inter-conversion of the four classes of alkali during cofiring. Assess the release characteristics of sodium and potassium during the cofiring. Observe eutectic melting phenomenon due to the interaction in cofiring. Abstract: Solvent fractionation, Laser induced breakdown spectroscopy (LIBS), X-ray Diffraction (XRD) and chemical analysis were applied to binary fuel mixtures of Zhundong coal and cornstalk agricultural class to investigate the release characteristics of alkali species during co-firing of coal and biomass. As the biomass proportion increases, the water-soluble, NH4 Ac-soluble and HCl-soluble alkali species interconvert; the extent of the conversion depends on the composition of the blend. From LIBS measurements, it was found that adding the biomass accelerates combustion and outgassing processes. The higher the proportion of the biomass in the blend, the earlier the peak concentrations of alkali appear, and the magnitude of peak concentrations of sodium and potassium decrease and increase, respectively. Furthermore, the interaction between coal and biomass can generate crystals causing the eutectic melting phenomenon (similar to feldspar in XRD results), which results in a sharp decline of the ash fusion temperatures (AFTs). The results not only provide the information of fundamental transformation but also guide industrial co-firing applications of lignite and agricultural class biomass to reduce the risk of ash deposition.